Enhanced Activation of Rac1/Cdc42 and MITF Leads to Augmented Osteoclastogenesis in Autosomal Dominant Osteopetrosis Type II. (16th July 2018) - Jung, Youn‐Kwan; Kwon, Ki‐Tae; Jang, Ji‐Ae; Han, Min‐Su; Kim, Gun‐Woo; Han, Seungwoo
ABSTRACT: The autosomal dominant osteopetrosis type II (ADOII) caused by the mutation of chloride channel 7 (ClC‐7) gene is the most common form of adult‐onset osteopetrosis. Despite dysfunctional bone resorption, an augmented osteoclast differentiation was reported recently in ADOII patients. DNA sequencing analysis of the ADOII patient's ClC‐7 gene identified a known heterozygous mutation, c.643G>A in exon 7, encoding p.Gly215Arg. In vitro osteoclast differentiation from the ADOII patient's peripheral blood mononuclear cells (PBMCs) increased compared with control despite their dysfunctional bone resorbing capacity. Osteoclasts from the ADOII patient's PBMCs and ClC‐7 knockdown bone marrow monocytes (BMMs) showed an enhanced Ser‐71 phosphorylation of Rac1/Cdc42 and increase of the microphthalmia‐associated transcription factor (MITF) and receptor activator of NF‐κB (RANK) that can be responsible for the enhanced osteoclast differentiation. © 2018 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of the American Society for Bone and Mineral Research.